REPRESENTATION OF BALINESE CULTURE ON THE AGA WHITE LABEL: A SEMIOTIC ANALYSIS - Hanindharputri, Made Arini; Irhandi, I Gusti Ngurah Gede Gita Yogi (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
The label design of Aga White by Hatten Wines incorporates local Balinese cultural elements into its visual communication, aiming to strengthen the product's identity as a tropical wine with a distinct cultural narrative. This study investigates how the label's visual elements, such as the coconut leaf illustration, sun motif, modern typography, and color palette, convey both denotative and connotative meanings, reflecting Bali's rich cultural values. Using Roland Barthes' semiotic theory, this research examines the denotative meanings, connotative symbolism, and the myths embedded in the label's design. The analysis highlights how the label constructs a narrative about harmony between nature and culture, emphasizing sustainability, local empowerment, and the spiritual connection between humans and nature. This study uses qualitative methods, including direct observation of the label, interviews with Hatten Wines representatives and designers, and secondary literature on branding and Balinese culture. The findings show that the Aga White label is not merely a product identifier but a tool for cultural representation, enhancing the consumer experience by linking the product to the cultural heritage of Bali. It concludes that branding based on local culture can provide an emotional connection with consumers while positioning a product in the global market. The integration of local culture into branding enhances product value, fosters a strong local identity, and provides a meaningful consumer experience.